Use of Modern Family Planning Methods in Fishing Communities of Lake Victoria, Uganda. - Annet Nanvubya; Julius Ssempiira; Juliet Mpendo; Ali Ssetaala; Annet Nalutaaya; Mathias Wambuzi; Paul Kitandwe; Bernard S Bagaya; Sabrina Welsh; Stephen Asiimwe; Leslie Nielsen; Fredrick Makumbi; et al. (PLoS ONE, 2015)
INTRODUCTION:Fishing communities (FCs) in Uganda have high HIV infection rates but poor access to health services including family planning (FP). Although FP is a cost-effective public health intervention, there is a paucity of data on knowledge and use of modern FP in FCs. This study determined knowledge and use of modern FP methods in FCs of Uganda. METHODS:Data were accrued from a 12-month follow up of 1,688 HIV-uninfected individuals, 18-49 years from 8 FCs along Lake Victoria, between September 2011 and March 2013. Data on knowledge and use of modern FP were collected through a semi-structured questionnaire. Prevalence Risk Ratios with corresponding 95% CIs were used to determine factors associated with Modern FP knowledge and use. RESULTS:The mean age was 31.4 years, with nearly half (48.8%) being females while more than half (58.6%) had attained up to primary education level. Knowledge of modern FP was high, 87.5% (1477/1688); significantly higher among females [adj. PRR = 4.84 (95% CI; 3.08, 7.61)], among older respondents (25-29 years) [adj. PRR = 1.83 (95% CI; 1.12, 2.99)] compared to younger ones (18-24 years) and among those conducting business [adj. PRR = 2.42(95% CI; 1.02, 5.74)] relative to those primarily in fishing. Just over a third (35.2%, 595/1688) reported use of at least one modern FP method. Use of modern FP methods was significantly higher among females [adj. PRR = 2.04 (95% CI; 1.56, 2.65, and among those reporting multiple sexual partnerships [adj. PRR = 2.12, 95% CI; 1.63, 2.76)]. Nonuse of modern methods was mostly due to desire for more children (30.6%), fear of side effects (12.2%) and partner refusal (5.2%). CONCLUSION:Despite their high knowledge of FP, FCs have low use of modern FP methods. Key barriers to use of modern FP methods were high fertility desires, fear of perceived side effects and partner refusal of methods.